y=x^2+2
y=-x+4
SOMEONE PLEASE HELP ME ON THIS

- anonymous

y=x^2+2
y=-x+4
SOMEONE PLEASE HELP ME ON THIS

- Stacey Warren - Expert brainly.com

Hey! We 've verified this expert answer for you, click below to unlock the details :)

- schrodinger

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

- anonymous

Equate the two equations, and then move everythign to one side so you have x^2+x-2. That factors into (x-1)^2=0, therefore x=1

- anonymous

Y=y, so x^2+2=-x+4
x^2+x-2=0
(x-1)(x+2)=0
x=1 or -2
Y=-x+4
y=-1+4. Or y=-(-2)+4
y=3 or y=6
so, x=1, y=3
or x=-2, y=6

- anonymous

@spaceknight ... after you get that 1 , do i plug that into x to get y ?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

&lotsobooks omg thanks . can you like tell me the steps on how you do it

- anonymous

lol oops i factored wrong sorry just listen to lotsobooks

- anonymous

i already solved this problem in the one before...

- anonymous

ok so can i ask you guys another question ? i need help on my entire algebra2 homework

- anonymous

you should try doing your own homework

- anonymous

&spaceknight i have been trying . if i knew how to do thiss i wouldntt be on my laptop asking for help . my teacher is the kind that doesnt like to explain too much .... I NEED HELP

- anonymous

Set both equations equal to one another.
Move all of the terms to the left side of the equation by adding or subtracting the terms on both sides of the equation.
Combine like terms.
Since it is a quadratic equation, you can factor it - use FOIL backwards, sort of.
Once you have the 2 possible values of x, then, you can substitute them back inti either of the original equations - I picked -x+4 since it is the easiest.
Then, calculate the values of y.
Remember to keep the x,y pairs together since they only go with one another.

- anonymous

see i never got instructions like that. ok how about this . im about to show you my next problem. im going to try and solve it by myself to see if i can do it but can you still help me

- anonymous

?

- anonymous

y=6x^2+5x+3
y==x+3

- anonymous

\[6x ^{2}+5x+3=-x+3\]

- anonymous

So far, so good.

- anonymous

ok so it will go like this i thinkk
6x^2+5x+3=-x+3
+x-3 +x-3
hold on i think i messed up

- anonymous

i got 6x^2+6x=0 when i subtracted

- anonymous

That is correct.

- anonymous

so what do i do now ?

- anonymous

In this case, it is easiest to subtract 6x from both sides.

- anonymous

then \[6x ^{2} = -6x ?\]

- anonymous

Right.
Then, divide both sides by 6.

- anonymous

ok so then that is x^2 = -1x
or x^2 = -x ?

- anonymous

Right.
Now, divide both sides by x.

- anonymous

ok so then after that x = -1 ?

- anonymous

Right.
Plug -1 into one of the original equations and solve for y.

- anonymous

so whenever i plug it into the second equation how do i do it ? do i ignore the negative there already is ?

- anonymous

No, keep the negative.
-(-1)+3=

- anonymous

wouldnt that 1 just turn into a positive ?

- anonymous

Right.

- anonymous

ok so it would be 1+3 so y = 4 ?

- anonymous

Yep.

- anonymous

We missed a second solution when I had you subtract 6x from both sides.

- anonymous

you are AWESOMEEEE !!!! :p thanks for helping meee

- anonymous

what step did we miss ?

- anonymous

Not a step so much as another solution.
At 6x^2+6x=0, it would have been better to factor 6x out.
So, 6x (x+1)=0
x=-1 or x=0.
then, y=4 or y=3.

- anonymous

You're welcome! Have fun!

- anonymous

:)

Looking for something else?

Not the answer you are looking for? Search for more explanations.